Steel and aluminium industry reactions of import rate announcement: Event study analysis - Anisyah Nur Kuswati; Faizah Syihab; Rizka Ramayanti (Economics, Business, Accounting & Society Review, 2022)
The study aims to find out the investor reaction to the announcement of import tariffs changes for the steel and aluminum sector. The study used the event study method, through the calculation of abnormal returns and trading volume activities which has the 11 event periods (ARCH/GARCH). The sample is public listed steel and aluminum firms, consist of daily stock prices, trading volume, and price index. One-sample test result showed abnormal returns variable are significant in the period before the announcement event, whereas the significant results only occurred on the period three after the event. Meanwhile, for the trading volume activities, the significant result show differences during the entire period. It can be said that the steel and aluminum industries being affected by the tariff announcement. As for two-samples test showed that there is not significant differences before and after the announcement event displayed, on abnormal returns and trading volume activity variable. Therefore, there is a shock influenced the stock return and show reaction by the announcement. From the study, abnormal return quickly returns to normal state and proved that the market in semi-strong efficiency category.